Wild Rice (ZIZANIA AQUATICA L): A Review - K Behera, Akshya; K Swain, Deepak (International Journal of Psychosocial Rehabilitation, 2025)
As the populace with an influx of industrialization and declining cropland, the price of plant genetic diversity is now recognised as becoming anindividualhabitation, which leads to food uncertainty in developing nations. Agricultural researchers discovered that PGD can be gathered& preserved in a bio archive, which retains genetic material, inprocedure of genetic resources (PGR), &like gene banks, &DNA libraries, &so on, for a long time. Spherically symmetric PGRs will, however, be used to boost crops to tackle future global food & nutritious safety problems. The genetic variability of the grains, yield for the plants, plant species, plant size of the feed yields, number of wheels per plant, number of main tillers leaves, average longitudinal and plant shelter percentages showed a considerable variability in diversetopographical regions. The average width of shrubberies&grains / husk ratios is of non-significant variability. The investigation demonstrates that in ten different collections the variability observed can be operated for cultivation in high-performance and non-safety crops. This section discusses four significant areas in detail; (i) the implication of seed biodiversity (PGD)&PGR in particular for ecologically relevant crops (mainly on the farm); (ii) stigmas correlated with the shrinking of established commercial plant classes& global warming genetic bases; In attempt to utilize new ways and new technologies for better besides rapid evaluation and use genetic plasma from mutation banks in their practicaltriggering programmes, this discussion helps the scientists.